The Effect of Work Competence, Workload, and Advertisy Intelligence on Employees' Performance, with Work Motivation as an Intervening Variable - Robertus Paulino Ndawa; Budiyanto Budiyanto; Budhi Satrio (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzed the effect of work competence, workload, and adversity intelligence on employees’ performance with work motivation as an intervening variable. Besides, it aimed to improve employees’ understanding and performance at KSP KOPDIT Mitan Gita in Maumere, Sikka. Moreover, the study was associative-quantitative with a correlational approach and path analysis, to examine the relationship among the variables on employees’ performance through work motivation. The population was 138 permanent employees at KSP KOPDIT Mitan Gita. Furthermore, the data were collected through questionnaires and documentation. The testing included validity, reliability, F-test, determination coefficient (R2), and t-test. As a result, the descriptive statistics test identified the significant effect of deadlines, work patterns, flexibility, and life needs on employees’ performance. Additionally, the result of validity and reliability was guaranteed (Cronbach’s alpha 0,60). The independent regression model was free from normality, multicollinearity, and heteroscedasticity. In addition, the result of the path analysis showed that work motivation was effective as a mediator with the best model (R2 56,56%). In short, work competence, workload, and adversity intelligence had a significant effect on employees’ performance at KSP KOPDIT Mitan Gita, with work motivation as an important mediator.